2010
DOI: 10.1186/1743-8977-7-28
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and persistence of pleural penetrations by multi-walled carbon nanotubes

Abstract: BackgroundMulti-walled carbon nanotubes (MWCNT) are new manufactured nanomaterials with a wide spectrum of commercial applications. The durability and fiber-like dimensions (mean length 3.9 μm long × 49 nm diameter) of MWCNT suggest that these fibers may migrate to and have toxicity within the pleural region. To address whether the pleura received a significant and persistent exposure, C57BL/6J mice were exposed by pharyngeal aspiration to 10, 20, 40 and 80 μg MWCNT or vehicle and the distribution of MWCNT pen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
221
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 217 publications
(233 citation statements)
references
References 38 publications
12
221
0
Order By: Relevance
“…The MWCNT in the airways may have resulted from direct deposition from the aerosol, as well as AM moving up the mucociliary escalator as part of the clearance process. In addition, our laboratory has previously reported that after pharyngeal aspiration of MWCNT, MWCNT penetrated the pleura (Porter et al 2010;Mercer et al 2010). Lastly, our laboratory has previously reported that 56 days after pharyngeal aspiration to MWCNT that inflammation had extended to the pleura, and MWCNT had penetrated the pleura.…”
Section: Discussionmentioning
confidence: 87%
“…The MWCNT in the airways may have resulted from direct deposition from the aerosol, as well as AM moving up the mucociliary escalator as part of the clearance process. In addition, our laboratory has previously reported that after pharyngeal aspiration of MWCNT, MWCNT penetrated the pleura (Porter et al 2010;Mercer et al 2010). Lastly, our laboratory has previously reported that 56 days after pharyngeal aspiration to MWCNT that inflammation had extended to the pleura, and MWCNT had penetrated the pleura.…”
Section: Discussionmentioning
confidence: 87%
“…The mechanism of fibre translocation out of the lungs into the pleural space and into the parietal pleura and diaphragm is not known but there is a wealth of literature to support the idea that a proportion of all particles and fibres deposited in the distal region of the lungs will translocate to the pleural space (reviewed in Donaldson et al 2010). Indeed, the penetration of CNT from the lung periphery through the visceral pleura into the pleural space after aspiration exposure has been quantified by Mercer et al 2010), who determined that 0.6% of the deposited fibre burden reached the visceral pleura.…”
Section: Discussionmentioning
confidence: 98%
“…More recently, investigators have demonstrated that well dispersed MWCNT are phagocytosed by macrophages following pulmonary exposure (Porter 2009;Ryman-Rasmussen et al 2009). The macrophages containing MWCNT can migrate to the subpleural space and enter the intrapleural space as early as as one day post-exposure (Hubbs et al 2009;Mercer et al 2010;Porter et al 2010). The MWCNT penetrate the intrapleural space and induce inflammation and fibrosis in a manner similar to asbestos (Ryman-Rasmussen et al 2009).…”
Section: Carbon Nanotube Treatment In Vivomentioning
confidence: 93%